Penilaian Hasil Penanaman Acacia crassicarpa menggunakan Plot Jalur dan Plot Lingkaran - Suhartati, Tatik; Sigiro, Elyas Frankly Gregorius; Wahyudiono, Sugeng; Purwadi (Jurnal Wana Tropika, 2025)
Plantation quality assessment is very important for evaluating the success of seedlings in growth, especially in industrial plantations. This study aims to determine the most effective and accurate plot sampling method for assessing the survival and stocking of Acacia crassicarpa. Two types of sampling plots were compared, namely line plots and circular plots, by recording the number of alive and dead plants, as well as measuring the time required for each plot. Statistical analysis was conducted to present statistical descriptions (mean, standard deviation, standard error, and sampling error). Additionally, an independent samples t-test was performed between plot types, preceded by a Levene's test for homogeneity of variances. The results showed that plant density assessments differed between line plots and circular plots. For survival, there was no significant difference between the two plot types. In terms of time efficiency, line plots were superior because the sample area consisted of straight lines, while circular plots took longer to implement, especially during moving from one to another plot. Therefore, the choice of method depends on the assessment objective. For assessing the success of the plants under study, the strip plot is more stable for assessing plant density